DAMPAK HAMIL PRA-NIKAH TERHADAP PERKAWINAN DINI: PERSPEKTIF SYARIAT ISLAM DAN HUKUM PERDATA DI KUA WURYANTORO, WONOGIRI - Affandi, Rohmad Sigid; Syamsuddin, S; Baehaqi, B (AL HUKMU: Journal of Islamic Law and Economics, 2023)
This study examines the issue of early marriage resulting from premarital pregnancy, analyzed from the perspectives of Islamic law and civil law in Indonesia, specifically focusing on cases recorded at the Office of Religious Affairs (KUA) in Wuryantoro District, Wonogiri Regency. The primary objective of this research is to analyze the legal and religious views on early marriage due to premarital pregnancy and to evaluate the role and policies implemented by KUA in handling such cases. The study identifies various contributing factors, including a lack of religious knowledge among the community, the influence of free association, insufficient parental supervision, and the limited guidance from religious leaders and government institutions on appropriate relationships between men and women. Furthermore, the research explores how Islamic teachings and Indonesian civil law respond to early marriage, particularly in terms of marriage regulations, age limits, and handling cases where marriage occurs due to pregnancy outside of wedlock. Using qualitative methods, including interviews, observations, and literature review, the study highlights the complex intersection between Islamic law and civil law in addressing early marriages due to pregnancy. The research recommends a comprehensive approach involving education, legal enforcement, and community engagement to reduce the incidence of early marriages and enhance public understanding of marriage laws and religious teachings. The findings of this study are expected to contribute both theoretically and practically to efforts aimed at preventing and addressing early marriages resulting from premarital pregnancy in Indonesian society.